Between field observations, notes and knowledge: Content and contexts for M. A. Castrén’s ethnographic notes and lectures - Lukin, Karina (Finnisch-Ugrische Forschungen, 2022)
This article discusses M. A. Castrén’s (1803‒1852) ethnographic notes and lectures on Samoyed peoples as part of the development of ethnography and Arctic research in the early 19th-century Russian Empire. Castrén produced several types of texts based on his two Russian expeditions, including travel narratives, letters, linguistic transcriptions and ethnographic notes. In addition, he gave lectures about the peoples he studied. The article describes the types of data Castrén collected, the way he organized it and subsequently presented to academic audiences. The academic and societal background of Castrén’s ethnography illustrated in the article, relates him to A. J. Sjögren and to the Imperial Russian and European development of ethnography. It is argued that the tensions between nationalistic aims and broader academic discussions that split Russian discussions over ethnography represented a fruitful context for imperial subjects, such as Castrén.